NEW APPROACHES TO STOMACH CANCER PREVENTION IN VIEW OF PERIODONTAL STATUS OF PATIENTS - S. V. Chuykin; T. V. Bashirova (Креативная хирургия и онкология)
Patients with gastric  ulcer, associated with Helicobacter pylori infection, have passed dental  examination and  gingivitis  and  periodontal treatment with  usage  of  lyophilized kumyss lactic acid bacillus and bismuth preparation. Measure time course  of dental  health (OHI-S, PMA, PDI). Diagnostic  examination methods – urease test, microbiological, serological,  molecular  genetic  examination methods before and after treatment. Complex treatment of gastric ulcer and inflammatory periodontal diseases locally in the oral cavity by kumysand bismuth-containing preparations.